Transcriptomic Profiling of Dental Pulp Pericytes: An RNAseq Approach - Yianni, Val; Sharpe, Paul T. (Frontiers in Dental Medicine, 2020)
Pericytes represent a population of mesenchymal cells that are found in virtually all vascularised organs where they share a range of similar features, mostly associated with vascular maintenance roles. It is becoming increasingly apparent that organ to organ differences exist between pericytes that directly relate to tissue-specific functions of these cells. Here, we present novel data indicating that in dental structures, pericytes have an immunomodulatory role. We show evidence supporting the concept that pericytes are a source of multiple cytokines and chemokines within the dental pulp, capable of regulating the extravasation of circulating lymphocytes. Using the SmartSeq-2 method we performed single cell RNA-seq and show that this is attributed to a defined pericyte sub-population that exists in vivo. In addition, as a consequence of our transcriptomic screen, we detect and validate a novel marker that can identify mature pericytes capable of giving rise to odontoblasts in vivo. Using transcriptomic screening, this marker is also identified to be expressed in pericytes residing in multiple other tissues including bone marrow, lung, and pancreas.